2019
DOI: 10.1246/bcsj.20190088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrolysis Susceptibility and Hydrophobicity of SN-38 Nano-Prodrugs on Their Anticancer Activity

Abstract: In the field of drug delivery, controllability of drug release site and duration are among the most important factors to manipulate the drug efficacy and side effects. In this paper, a series of nano-prodrugs (NPs) composed of anticancer agent SN-38 and various substituent groups were synthesized and fabricated. By increasing the hydrophobicity of the prodrug molecule (calculated logP values exceeded ca. 7) through changing the substituent group, the hydrolysis susceptibility of SN-38 NPs in mouse serum was dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Notably, SN-38-NPDs were found to have about 10 times higher efficiency than Irinotecan (the clinically used water-soluble prodrug of SN-38). 8 Despite their impressive therapeutic efficiency, the lack of knowledge concerning the intracellular fate, degradation, and conversion into the active drug of NPDs after internalization drastically hinders further developments towards clinical applications. Here, we report a comprehensive study on the dynamics of SN-38-NPDs inside cancer cells, which includes internalization rate, intracellular localization, and degradation of SN-38-NPDs, as well as their therapeutic efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, SN-38-NPDs were found to have about 10 times higher efficiency than Irinotecan (the clinically used water-soluble prodrug of SN-38). 8 Despite their impressive therapeutic efficiency, the lack of knowledge concerning the intracellular fate, degradation, and conversion into the active drug of NPDs after internalization drastically hinders further developments towards clinical applications. Here, we report a comprehensive study on the dynamics of SN-38-NPDs inside cancer cells, which includes internalization rate, intracellular localization, and degradation of SN-38-NPDs, as well as their therapeutic efficiency.…”
mentioning
confidence: 99%
“…Thanks to their colloidal stability and high therapeutic efficiency, SN-38-NPDs prepared from SN-38-chol were chosen as a model nanoparticle and synthesized according to the established protocol. 8 A similar protocol has been adopted to fabricate SN-38-NPDs containing BODIPY FL fluorescence probes (FRET-NPDs) for FRET-based experiments. 14,15 For the preparation of FRET-NPDs by reprecipitation, the water solubility of BPFL was lowered by modifying the carboxylic group with a cholesterol moiety (BPFL-chol).…”
mentioning
confidence: 99%
“…CLS NPs were prepared by a reprecipitation method, according to the previously published protocol. 28 In brief, CLS was completely dissolved in THF solution (10 mM) under sonication. Next, 400 μL of CLS solution was rapidly injected into the stirring water (10 mL) using a microsyringe, resulting in a 0.4 mM CLS NP dispersion.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a small part of SN-38 formed after hydrolysis is introduced in mitochondria and nucleus, effectively inducing cell damage that leads to cell death. 28,29 4.3. Overall Intracellular Behavior of CLS NPs Observed by Raman and Autofluorescence.…”
Section: Cellular Effects Of Cls Npsmentioning
confidence: 99%
“…For example, Lee et al 33 prepared the pure nanodrugs using curcumin as model drug with controllable size ranging from 20 to 200 nm through an ice-template-assisted approach as shown in Figure 2, which has the potential of extending to other hydrophobic therapeutic drugs. For drug derivatives, Kasai et al 34 reported that anticancer agent SN-38 modified by different fatty acids with different hydrophobicity could assemble into nanoparticles with different sizes. However, no correlation of particle size and hydrophobicity has been observed by the reprecipitation method.…”
Section: Small Molecule Nanodrugs Overcoming In Vitro "Barriers"mentioning
confidence: 99%